Considering the concept of nutritional modification coupled with phytase supplementation for reducing Campylobacter jejuni in broilers - Gibbs, Kirsty; Bello, Abiodun; van der Klein, Sasha; Poulsen, Charlotte; Kragh, Karsten; Marchal, Leon (Frontiers in Veterinary Science, 2025)
Campylobacter jejuni remains a significant health concern in humans, with the consumption of contaminated poultry meat being the primary source. Nutritional virulence could be utilized to help reduce Campylobacter in poultry, specifically by reducing dietary iron (Fe) and phosphorus (P), which appear to be essential for Campylobacter growth and persistence, in combination with phytase supplementation to meet bird mineral requirements. We discuss the scientific basis of this hypothesis and present results of a small-scale proof-of-concept broiler study comprising: (1) control: mixed grain commercial diet; (2) added Fe- and inorganic phosphate (iP)-free premix: as control but formulated without Fe in the mineral premix and without added iP, with increased phytase [phytase unit (FTU)/kg per phase] and higher associated matrix values for Ca, metabolizable energy (ME), and digestible amino acids (AA) vs. control. Over the 42-day (d) trial, birds exhibited similar (non-significantly different) livability and growth performance. Average cecal Campylobacter loads were numerically 7.7-fold lower (87% reduction) in the added Fe- and iP-free treatment relative to the control [4.90 × 107 colony forming units (CFU)/g vs. 3.78 × 108 CFU/g, respectively; p-value = 0.12]. In addition, the range in recorded loads of Campylobacter was wide in both treatments, but the upper end of the range was 1 log10 units lower in added Fe- and iP-free vs. control (2.97 × 109 vs. 2.45 × 1,010), which suggests a reduced upper limit of colonization and reduction in average Campylobacter levels. Although caution is warranted on the numerical results, we believe they should encourage further ideations, investigations, and larger scale applications in the future.